Relationship between Students’ Metacognitive Strategy and Self-Efficacy in Speaking - Adam Adam (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The main purpose of this research is to investigate the relationship between students’ metacognitive strategy and their self-efficicacy in speaking skills. Besides, this study also investigates the overall level of students’ use of metacognitive strategy and the level of their self-efficacy in speaking skills. The sample of this research was the eighth grade students of SMP 26 Batam in the academic year 2016/2017. The data were collected using questionnaires and were calculated using a Likert Scale. There were three findings of this research. First, The overall level of students’ metacognitive strategy in speaking skills was 3.3. Second, the overall level of students’ self-efficacy in speaking skills was 3.27. Third, there was a positive correlation between students’ metacognitive strategy and their self-efficicacy in speaking skills which was indicated by the correlation coefficient of 0.54. There is a significant correlation between students’ metacognitive strategy and their self-efficacy in speaking skills as indicated by the correlation coeficient of 0.54. There is a positive direction of the correlation as indicated by the correlation coeficient above zero and near to 1. The students’ overall metacognitive strategy use in speaking skills is a medium level as indicated by the mean score of 3.3 The students’ overall self-efficacy in their speaking skills is a medium level as indicated by the mean score of 3.27. Keywords : metacognitive, self-efficacy, speaking skills